THE INVESTIGATION OF PARENTS’ PERSPECTIVE TOWARDS THE IMPORTANCE OF ENGLISH LEARNING AT PRIVATE ISLAMIC SCHOOLS IN MAKASSAR - Ary Putra Sanusi (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The current school curriculum is seen to have far too many disciplines to cover. In general, there are three types of courses taught in middle and high school: general subjects, science subjects, and social subjects. This subject group really grows in Islamic schools when religious subject groups are present. The concentration of learning that students must follow is a phenomenon as a result of so numerous disciplines. According to prior research, this attention is kept by parents of children who have particular expectations of them. This paper is the result of an investigation into Parents' Perspective towards the Importance of English Learning at Private Islamic Schools in Makassar. The research reveals that some parents who think that learning English is not too important, tends to be unimportant or even not important at all compared to religious learning where they give the doctrine directly to their children (students) or indirectly by not showing the appreciation for the results of learning English the children get